High-dosage short-term corticotrophin therapy in acute asthma. Issue 4 (July 1969) - Glick, I. W.; Friedman, M.
Abstract : The effect of corticotrophin suspended in gelatin in doses varying from 40 to 400 i.u. on the plasma 11-hydroxycorticosteroid response has been investigated in volunteer subjects in order to determine the optimum dose required to produce prolonged and continuous adrenocortical stimulation using this preparation. Increasing the dose of corticotrophin beyond 200 i.u. did not produce a greater intensity or prolongation of adrenocortical stimulation; 300 i.u. corticotrophin in 7·5 ml. of gelatin produced the same effect as 310 i.u. in 1 ml. gelatin. In order to achieve prolonged and continuous adrenal stimulation the optimum dose of corticotrophin would appear to be 200 i.u., which could be suspended in 1 ml. of gelatin for ease of administration, and which produced adrenal stimulation for approximately 36 hours. The effect of the administration of a single large dose of corticotrophin has been investigated in 13 asthmatic patients during an exacerbation. All had failed to respond to conventional therapy but responded to corticotrophin with one exception. Five patients required no more than two injections for a sustained remission. Seven were discharged needing prolonged corticotrophin in conventional doses. The advatage of using this form of corticotrophin therapy over a short course of high-dosage corticosteroid therapy is discussed.